Paget's disease of the male breast with underlying ductal carcinoma in situ (‘DCIS’) - Choudhury, Bhuban (J Surg Case Rep, 2015)
Male breast cancer accounts for 1% of all breast malignancies and 0.1% of all male cancer death. Like Paget's disease, DCIS is a rare form of male breast malignancy. We report a 69-year-male presenting with 3 years history of subtle of nipple symptoms and normal breast imaging. Punch biopsy of nipple established the diagnosis of Paget's disease and subsequent histology of mastectomy specimen revealed underlying DCIS.